2022-RA-1344-ESGO Endometrial cancer patients with an overexpression of the orphan nuclear receptor NR2F6 show an improved survival. (20th October 2022) - Proppe, Louisa; Jagomast, Tobias; Ribbat-Idel, Julika; Beume, Sophie; Gitas, Georgios; Hemptenmacher, Franziska; Rody, Achim; Perner, Sven; Hanker, Lars Christian
Abstract : Introduction/Background: NR2F6 (nuclear receptor subfamily 2 group F member 6, also called Ear-2) is known to be an orphan nuclear receptor being an intracellular immune checkpoint in effector T cells. It might play an essential role for tumor development and growth. Therefore, the prognostic impact of NR2F6 in endometrial cancer is evaluated in this study. Methodology: Expression analysis of NR2F6 in 142 endometrial cancer patients was performed by immunohistochemistry. Staining intensity of tumor cells was computerized assessed semi-quantitatively, and results were correlated with clinicopathological characteristics and survival. Results: 46 of 117 evaluable samples (39.3%) showed an overexpression of NR2F6, leading to an improvement of the overall (OS) and disease-free survival (DFS). In NR2F6 positive patients, the mean OS was 156.6 months (95% confidence interval (CI): 142.4 – 170.8) compared to 105.8 months in NR2F6 negative patients (95% CI: 85.6 – 125.9; p = 0.025). The disease-free survival differed by 58.4 months (156 months (95% CI: 142.2 – 169.9) vs. 97.6 months (95% CI: 74.7 – 120.6), p = 0.004). Furthermore, we found significant associations between NR2F6 positivity, MMR status, and PD1 status. A multivariate analysis suggests NR2F6 to be an independent factor influencing the disease-free survival ( p = 0.037). Conclusion: This is the first report on the prognostic impact of NR2F6 in endometrial cancer patients. We could demonstrate that there is a significant better progression-free and overall survival for patients with overexpression of NR2F6 in patients with endometrial cancer. Further studies are required to validate its prognostic impact.